Microfluidic systems for neural tissue engineering - CESUR, SÜMEYYE; ULAĞ, SONGÜL; GÜNDÜZ, OĞUZHAN (Elsevier Science, Oxford/Amsterdam, 2023)
Damage to the nervous system due to illness or injury can cause serious and lasting loss of function or even fatal consequences. It is necessary to develop new treatment strategies to restore the function of the damaged nervous system.The optimal environment for nerve cell proliferation and differentiation is provided by neural tissue engineering. It aims to improve a new approximation for the therapy of nervous system diseases. Compared to 2D cell culture techniques, 3D cell culture systems ensure a more biomimetic environment and encourage more differentiation of cells. However, certain cell culture parameters have limitations in spatio-temporal control. With the advent of microfluidic systems, it can control the spatio-temporal dispersion of physical and chemical signals at the cellular level. In this section, microfluidic systems are explored as a tool to target both physical and chemical injury and recreate the post-injury environment, to study nerve injury at the cellular grade.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)